Introduction to the Economics of Religion - Iannaccone, Laurence R. (Journal of Economic Literature, 1998)
After a very long hiatus, economists have begun again to study the relationship between economics and religion. This article seeks to summarize and evaluate the principal themes and empirical findings that have appeared in some 200 recent papers on the economics of religion. Although some of the research concerns the economic consequences of religiosity, most applies standard economic theory to the study of individual religious activity, the characteristics of religious groups, and the impact of regulation and competition on religious markets.